Enabling stakeholder participation in marine spatial planning: the Bangladesh experience. Issue 3 (1st September 2020) - Mannan, Samsul; Nilsson, Henrik; Johansson, Tafsir; Schofield, Clive
ABSTRACT: The article explores stakeholder participation in marine spatial planning with particular reference to Bangladesh, a country which has committed to developing such an ocean management approach but remains at an early stage in the process. A contextual overview of the marine environment, resources and economic activities within the maritime areas of Bangladesh is provided. Definitions and concepts of marine spatial planning are critically discussed and the need to identify and understand the roles, expectations and interests of diverse stakeholders to deliver successful implementation emphasised. An overview and synthesis of a survey of maritime stakeholders in Bangladesh is provided with a view to enhancing understanding of their engagement processes, relationships and conflicts. Recommendations to reconcile conflicting uses and help facilitate the development of marine spatial planning in Bangladesh and potentially the Bay of Bengal more widely.